(untitled) (مجلة إحالات, 2026)
This study attempted to approach the novel "Ebola 76" by Sudanese novelist Amir Taj al-Sir, not from the perspective of the pandemic’s theme or subject matter, but from within the language of the creative work itself towards which, life expands with its pains and hopes, sorrows and joys. Therefore, the pandemic becomes more than just a content, as it is embodied in the style or expression, taking on the character of an event characterized by seriousness and authenticity